Design of Anti-Interference Digital Circuits for UART Communication - Jin, Linxi (Computers and Artificial Intelligence, 2025)
This paper designs and implements a UART receiving module with anti-interference capability based on Verilog HDL. During the design process, the working principle of the UART protocol was first analyzed in depth, clarifying the data frame structure and baud rate sampling mechanism. On this basis, a receiving module was constructed, incorporating functions such as start-bit detection, baud-rate division, data-bit acquisition, and stop-bit verification. In addition, multi-point sampling and majority-voting logic were introduced to effectively suppress input interference signals. Simulation results demonstrate that under simulated interference conditions, the receiving module can correctly parse serial data, providing stable and reliable output with significant anti-interference performance. This design ensures communication accuracy while maintaining extensibility, thereby offering a feasible reference for the development of subsequent embedded system communication modules.